KONSEPSI OTONOMI DAERAH SEBAGAI ALTERNATIF PILIHAN DARI TUNTUTAN BENTUK NEGARA FEDERAL DI INDONESIA - Ginting, Darwin (Sekolah Tinggi Hukum Bandung, 2011)
Since the fall of the New Order regime, the courage to sue the state began to reverberate dipentas unitary national politics. The emergence of the idea of a federal state (united state) is the antithesis of the implementation of regional autonomy in Indonesia based on Law No.5 of 1974 on the Principles of Local Government is in the very setralisti. Through these legal instruments are the restraints and the dominance of local independence done so strict and systematic. Though conceptually the real regional autonomy is the freedom of movement (of expression) should be given to the autonomous regions to conduct their own initiatives to manage the interests of society in the region. Therefore there is a presumption that the imposition of the concept of regional autonomy through the form of a unitary state did not take the welfare of people in the region because the laws on local government implementation of the new order which is conceptually very repressive, also followed well as the behavior of authoritarian governments, harassing human rights, setralisme power sucking resources into the central region. To overcome this, then the solution is the democratization and decentralization of power through regional autonomy the broadest, not by changing the form of the state of federalism, but by changing the way state officials are concerned interestexistence of regions including the utilization of natural resources equity and pluralism (diversity) regions. This is where the importance of regional autonomy as one of the vanguard of the unitary Republic of Indonesia guard.Keywords: Unitary - Federal - Regional Autonomy